Respuesta :

Answer:

Step-by-step explanation: Sorry no time gtg : / (if you really need it I'LL ANSWER TOMMOROW

Answer:  The required simplified expression is -6xy.

Step-by-step explanation: We are given to simplify the following rational expression :

[tex]E=-\dfrac{18x^2y}{3x}~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]

We will be using the following property of exponents :

[tex]\dfrac{z^a}{z^b}=z^{a-b}.[/tex]

From expression (i), we get

[tex]E\\\\\\=-\dfrac{18x^2y}{3x}\\\\\\=-\dfrac{18}{3}x^{2-1}y\\\\=-6xy.[/tex]

Thus, the required simplified expression is -6xy.